Factor Analysis of Family Member Behavior to Wards Giving Therapy Anti Retrovial (ARV) in Children With HIV/ AIDS in RAA Soewondo Hospital Pati - nisa, Makzizatun nisak; Budi Raharjo, Bambang; Ratna Sri Rahayu, RR (Public Health Perspective Journal, 2019)
Background: HIV is one of the major health problems and infectious diseases that can affect maternal and child mortality. HIV / AIDS in Indonesia from year to year is constantly increasing. Not a few people with this deadly virus is that they are still considered children. Children with HIV / AIDS in order to stay healthy immune system can be arrested by taking anti-retroviral / ARV. They are only successful if used in compliance, according to the schedule. The award of ARV therapy in children should be appropriate to the child can sustain life in the long term so that the child requires special attention and depending on the behavior of family members Method: This study used a qualitative approach, descriptive research type. The research object is the provision of antiretroviral therapy in HIV / AIDS. Subjects were parents and families of children with HIV / AIDS. Research with in-depth interviews. Qualitative data processing performed by the content analysis method based on a theme (thematic content analysis). Result: The primary informants in this study had a lifespan of 25 years up to 47 years. The education levels of primary informant school no 3, SD 1, SMA 2 and D2 1. Knowledge of HIV and antiretroviral mostly know about HIV is an infectious disease that attacks the immune system. ARVs are drugs to treat HIV / AIDS. Access to VCT / PMTCT distance from the house to the hospital where taking antiretrovirals majority of informants has a considerable distance to the point of taking ARV (over 20 km). Means of transportation used for the majority of health facilities to the motorcycle itself. Family Support shows that 4 immediate family informant know about the child's illness and provide support and attention. Children with HIV / AIDS have different accuracy in the delivery of antiretroviral therapy, most of the regular informant, at the same time, precise and has never been forgotten in the provision of antiretroviral therapy are 5 key informants. There is one informant who had never done ARV treatment. The remaining one informant said he had about 6 months did not take antiretroviral drugs to the hospital so do not take medication again. Conclusion: Most informants regularly taking antiretrovirals, at the same time, precise and has never been forgotten in the provision of antiretroviral therapy are 5 key informants. 1 informant who have never done ARV treatment. The remaining one informant said he had about 6 months did not take antiretroviral drugs to the hospital so do not take the medicine again. ARV consumption in children with HIV / AIDS is highly dependent on family members who care for children.